Sonographic assessment of normal cervical lymph nodes in a sample of Syrian population - Al-Ani, Rand Sh; Mashlah, Ammar M; Al-Hafar, Mohammad Iyad (Journal of Baghdad College of Dentistry, 2013)
Background: Sonographic examination is an important tool in assessment of normal and abnormal cervical lymph nodes. The aim of the study is to assess the distribution and the characteristic features of normal cervical lymph nodes in a sample of Syrian population. Materials and Methods: Fifty healthy Syrian subjects (25 men and 25 women) with an age of 20 -60years old, who had their cervical lymph nodes examined by ultrasound. Three hundred and two lymph nodes were detected. Lymph nodes were evaluated for their number, size, site, echogenic hilus, shape, as well as for the border sharpness. The subjects were categorized by age into four groups, (20 -30, 31 - 40 , 41 - 50 , 51- 60 years ). Statistical analysis of data was done using SPSS software (version 11.5), and analytical one way analysis of variance (ANOVA), Duncan’s Multiple Range Test. Results: The results showed that there was no significant difference in mean number of nodes between different age groups. All lymph nodes were hypoechoic; majority of them possessed an echogenic hilus, with transverse diameter of 8 mm or less. All lymph nodes were oval except for submandibular and parotid nodes which appeared round. Conclusions: This study provides a sonographic appearance of normal cervical lymph nodes in relation to their site, size, shape, numbers, border sharpness, and echogenic hilum, in a sample of Syrian population.